2015
DOI: 10.4103/0366-6999.156773
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Domestic Leuprorelin in Girls with Idiopathic Central Precocious Puberty

Abstract: Background:In central precocious puberty (CPP), the pulse secretion and release of gonadotropin-releasing hormone (GnRH) are increased due to early activation of the hypothalamic-pituitary-gonadal axis, resulting in developmental abnormalities with gonadal development and appearance of secondary sexual characteristics. The CPP without organic disease is known as idiopathic CPP (ICPP). The objective of the study was to evaluate the clinical efficacy and safety of domestic leuprorelin (GnRH analog) in girls with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…This treatment would have reversible changes to BMI, reproductive system and bone density (10); although it would not result in decreasing the bone quality and quantity after menarche (11-12). Patients treated with the GnRH agonist may report vaginal bleeding for 3 to 5 days, especially 2 weeks, after initiating the treatment (5). Moreover, increased appetite was observed in children who were treated with the GnRH agonist (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment would have reversible changes to BMI, reproductive system and bone density (10); although it would not result in decreasing the bone quality and quantity after menarche (11-12). Patients treated with the GnRH agonist may report vaginal bleeding for 3 to 5 days, especially 2 weeks, after initiating the treatment (5). Moreover, increased appetite was observed in children who were treated with the GnRH agonist (13).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with the gonadotropin-releasing hormone agonist (GnRH) agonist is a healthy, relatively old treatment (4). Most of the complications of this treatment are manifested as pseudo-menopausal in children (5). However, thyroid hormones disorders are considered to be the complications of treatment with the GnRH agonist which has been neglected in pediatric studies, and is mostly studied in adults and cases other than precocious puberty (6).…”
Section: Introductionmentioning
confidence: 99%
“…It acts on the pituitary in a continuous nonpulsed form, downregulates its GnRH receptor or reduces its sensitivity to the GnRH receptor, and inhibits the pituitary to secrete luteinizing hormone (LH) and follicle stimulating hormone (FSH), thus inhibiting the development of secondary sex characteristics [ 10 , 11 ], achieving the effect of therapeutic precocious puberty. Although leuprolide plays a significant role in the treatment of precocious puberty, it has been found that it is easy to cause vaginal bleeding when used for the first time, with an incidence of 16%–60% [ 12 ]. Also, it can also increase the incidence of polycystic ovary syndrome [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It acts on the pituitary in a continuous non-pulsed form, down-regulates its GnRH receptor or reduces its sensitivity to GnRH receptor, and inhibits the pituitary to secrete luteinizing hormone (LH) and follicle stimulating hormone (FSH), thus inhibiting the development of secondary sex characteristics [10,11] , achieving the effect of therapeutic precocious puberty. Although leuprolide plays a significant role in the treatment of precocious puberty, it has been found that it is easy to cause vaginal bleeding when used for the first time, with an incidence of 16%-60% [12] . And it can also increase the incidence of polycystic ovary syndrome [13] .…”
Section: Introductionmentioning
confidence: 99%